Implementação de uma amostra atômica fria 2D para o estudo do espalhamento de luz em regimes densos bidimensionais - Martins, Matheus do Amaral (Universidade Federal de São Carlos, 2025)
In this dissertation, an intermediate step is presented toward the implementation of a two-dimensional (2D) cold atomic sample aimed at studying light scattering in dense regimes. The work focuses on the development and characterization of an experimental system capable of manipulating and compressing a cold trap of strontium-88 (⁸⁸Sr) atoms using an optical dipole trap and an interference pattern known as an optical accordion. Additionally, a feedback system was implemented to correct the position of the interference pattern, ensuring the stability required for future experiments. Simulations were carried out to predict the characteristics of the new trap and to assess the feasibility of studying light-matter interaction in this regime. The results indicate a significant increase in the spatial density of the atomic cloud, along with an improvement in the system’s optical depth, making it more suitable for investigating collective phenomena in the dense regime.
Implementation of a 2D cold atomic sample for the study of light scattering in dense two-dimensional regimes
Keywords: Átomos frios; Aprisionamento atômico; Espalhamento coletivo de Luz; Cold atoms; Light-matter interaction; Collective scattering of light; CIENCIAS EXATAS E DA TERRA::FISICA